Renal Perinephric Abscess Complicated with Psoas Muscle Abscess - D, Kochiashvili; T, Didbarize; V, Kvakhajelidze; G, Kochiashvili (Journal of Medical Biomedical and Applied Sciences, 2018)
Perinephric abscess is an uncommon complication of urinary tract infections. The incidence ranges from 1-10 cases for every 10000 hospital admissions. Men and women are affected with equal frequency. Escherichia coli, Proteus speacies and Staphylococcus aureus are the unusual etiologic organisms. There were very few reports about urinary tract infections such as renal perinephric abscess complicated with psoas muscle abscess.Renal and perirenal abscess can complicate aurologic infection (usually due to gram-negative enteric bacilli or a polymicrobial infection). This clinical case of a 24 year old men with predisposing condition for secondary psoas muscle abscess (6 year history of the right non functional kidney), is interesting because of unusual etiologic organisms for psoas muscle abscess Proteus mirabilis, which is highly flagellate, have stone formation ability which is very difficult to clear with only antibiotics, has predilection for the kidney and are difficult to eradicate.